Determinants of Interest and Intention To Donate Cash Waqf or Through Money on The Super App Berkahwakaf.Id - Muhamad Neko Maulana; Hermanto Siregar; Imam Teguh Saptono (Jurnal Aplikasi Bisnis dan Manajemen, 2025)
Background: Cash waqf and waqf through money is an unfamiliar concept in donation activities in Indonesia. Cash waqf possesses a sustainable nature, as the endowed assets are preserved and managed to generate ongoing benefits across generations. This sustainability is ensured by the obligation of the nazhir to safeguard the waqf assets from loss or damage, thereby maintaining their long-term impact. Purposes: This research aims to explore public interest and intention in cash waqf and analyze the factors influencing the community's interest and intention toward cash waqf. Design/methodology/approach: The statistical method employed is descriptive analysis and structural equation modeling with partial least squares (SEM-PLS), using tool Smart PLS version 4 with 70 respondents. The respondent category in this study is muslim or Muslimah, has ever performed monetary waqf, and is at least 17 years old.Findings/Result: The analysis reveals that the respondent living or working in Jakarta prioritizes engaging in waqf through money, followed by cash waqf. Statistical test results indicate that performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, price value, habit, and waqf literacy all have a positive and significant effect on behavioral intention. Conclusion: The results of the descriptive analysis show that respondents living or working in Jakarta are more interested in donating waqf through money compared to cash waqf. The waqf literacy index is 72.81% (moderate), the basic understanding of waqf is 47.83%, and the advanced understanding of waqf is 24.98%. The statistical test results indicate that performance expectations, effort expectations, social influence, facilitating conditions, hedonic motivation, price value, habits, and waqf literacy all have a positive and significant impact on behavioral intention.Originality/value (State of the art): The state of the art in this study is the use of the UTAUT2 variable, which has been cited more than 6,000 times on Google Scholar and has never been previously used to analyze the impact of technology adoption in cash waqf collection through Berkahwakaf.id. Keywords: cash waqf, SEMPLS, super apps, UTAUT2, waqf literacy